Host Parasite Interaction of Apicomplexan Parasites (Sporozoa: Haemosporida) in Columba livia - Mohammad Shoeb2, Nasim Jahan1* and (Journal of Experimental Sciences, 2010)
<div style="border-right: medium none; padding-right: 0in; border-top: windowtext 1pt solid; padding-left: 0in; background: white; padding-bottom: 0in; border-left: medium none; padding-top: 1pt; border-bottom: medium none; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> ABSTRACT: During thirty nine months of sampling, the prevalence was studies in C. livia of Rohilkhand region of Uttar Pradesh, India, according to the sex of the host, different seasons and localities where the pigeons were obtained. Data on the occurrence of Haemoproteus and Plasmodium showed the maximum percentage of infection (55.63%) in C. livia during the entire period of study. Out of 266 pigeons sampled, 148 pigeons were positive for Haemoproteus at a prevalence of 55.63%. Only 18 pigeons (2.67%) had a mixed infection with Haemoproteus and Plasmodium and 130 pigeons (48.87%) had Haemoproteus infection alone and no pigeons were positive for Plasmodium alone. Parasite incidence in relation to the sex of the host indicated a higher infestation in females (62.79%) than males (57.65%). The overall highest infectivity of parasites was recorded during the summer season (82.85%) followed by spring season (59.37%) and least in the winter season (42.30%). It was also observed that Haemoproteus occurred at diverse infectivity in C. livia from different localities (Badaun-51.35%, Bareilly- 11.18% and Shajahanpur-58.06%) whereas Plasmodium was recorded 11.18% only from Bareilly. This parasite was completely absent from the other two sites. Key words: Haemoproteus, Plasmodium, pigeons, prevalence, seasons, sex 1Department of Life Science, R.K.S. Degree College, Sahawar Kanshiramnagar 207245 (U.P.) India; 2Department of Zoology, Sir M.U.Degree College, Sahawar Kanshiramnagar 207245 (U.P.) India Please Cite This Article As: Nasim Jahan and Mohammad Shoeb. 2010. Host Parasite Interaction of Apicomplexan Parasites (Sporozoa: Haemosporida) in Columba livia. J. Exp. Sci. 1(5):6-10.